Algorithmic Bricks: A Tangible Robot Programming Tool for Elementary School Students - Kwon, Dai-Young; Kim, Han-Sung; Shim, Jae-Kwoun; Lee, Won-Gyu (IEEE transactions on education, 2012)
Tangible programming tools enable children to easily learn the programming process, previously considered to be difficult for them. While various tangible programming tools have been developed, there is still a lack of available tools to help students experience the general programming process. This study therefore developed a tool called Algorithmic Bricks (A-Bricks), to improve the programming language experience by considering and utilizing characteristics of procedural language. Specifically, elements such as sequence, repetition, condition, function, and parameter were used to develop A-Bricks. In addition, this study observed the benefits of A-Bricks and confirmed its potential as a tangible educational programming tool by comparing and analyzing elementary school students using A-Bricks to control groups using Scratch.